Tidying things up: Tropicosa, a new Neotropical wolf spider genus (Araneae: Lycosidae: Lycosinae) - Paredes-Munguía, Williams; Brescovit, Antonio D.; Teixeira, Renato A. (Zootaxa, 2023)
The new genus Tropicosa is proposed based on species of some controversial Neotropical genera of lycosids. These spiders present a longitudinal dark stripe over the sternum in both sexes, median apophysis sinuous, tegular lobe evidently sclerotized and the epigyne with median septum anteriorly expanded and with a parallel, triangular hood. We transfer Alopecosa moesta (Holmberg), Schizocosa chelifasciata (Mello-Leitão) and Lycosa thorelli (Keyserling) to Tropicosa gen. nov. and describe one new species, Tropicosa baguala sp. nov. Likewise, Arctosa bogotensis (Keyserling) is synonymized with Tropicosa thorelli (Keyserling) comb. nov., and Lycosa langei Mello-Leitão with T. chelifasciata (Mello-Leitão) comb. nov. based on examined types. All the four species proposed as members of Tropicosa gen. nov. have South American distribution.